PENGARUH PDB, INFLASI, DAN SUKU BUNGA TERHADAP INVESTASI PORTOFOLIO ASING DI INDONESIA PERIODE 2014-2023 - Erwinsyah, Hendi; Wiralaga, Harya Kuncara; Sebayang, Karuniana Dianta Arfiando (Jurnal Serambi Ekonomi dan Bisnis, 2024)
Foreign portfolio investment is one of the foreign investment flows that has a major contribution to the running of the economy in a country. This study aims to determine the effect of GDP, inflation, and interest rates on foreign portfolio investment in Indonesia. The analysis method used is multiple linear regression using time series data for the period 2014Q1 - 2023Q4. The data used is obtained from the website of Bank Indonesia, Badan Pusat Statistika (BPS), Trading Economics, and CEIC Data. The results showed that GDP has a positive and significant effect on foreign portfolio investment. In addition, inflation also has a positive and significant effect on foreign portfolio investment. Meanwhile, interest rate has a negative and significant effect on foreign portfolio investment. In the simultaneous test, GDP, inflation, and interest rates together have a significant effect on foreign portfolio investment in Indonesia.